STRATEGI PENGHIMPUNAN DANA SOSIAL UMMAT PADA LEMBAGA-LEMBAGA FILLANTROFI DI INDONESIA (Studi Kasus Dompet Peduli Ummat Daarut Tauhid, Dompet Dhuafa Republika, BAZNAS, dan BAZIS DKI Jakarta) - N.Oneng Nurul Bariyah (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
Abstract This study aimed to describe forms of fundrising conducted by institutions fillantrofi in Indonesia. The study was conducted at four institutions namely DPU Daarut Tauhid, Dompet Dhuafa Republika, BAZNAS, and BAZIS of DKI Jakarta. Source of data obtained from interviews and documentation. Data was analyzed using qualitative deskripstif. The results showed that the forms of fund raising undertaken, namely: Media usedprint, electronic, internet, and media communication. In this case there are several ways, namely: Media compaign, direct mail, telefundrinsing, direct fundrising, cooperation program, special event, religious fund, zakat collectors forming units (UPZ), CSR and CSR Cooperation Program, donation ritail humanitarian fund, through bank: ATM (transfers, phone and internet banking), service zakat donations via SMS and online. Keywords: Fundrising, humanitarian, cooperationand service donation.